P300 decrements in teenagers with conduct problems: implications for substance abuse risk and brain development - Bauer, Lance O; Hesselbrock, Victor M (Biological psychiatry (1969), 1999)
Background: The purpose of this study was to evaluate the effects of conduct disorder problems, family history, gender, and age on P300 electroencephalographic potentials in teenagers. Methods: The 257 subjects, aged 15 to 20 years, were assigned to one of twelve groups defined by the crossing of three between-subjects factors: 1) gender; 2) ranking below vs above the median number of conduct disorder problems for their gender; and 3) no family history of alcohol or drug dependence vs familial alcohol dependence vs familial heroin or cocaine dependence. Results: P300 amplitude was smaller among subjects reporting a greater number of conduct problems prior to age 15 vs those reporting fewer problems of this type. No family history effects were detected. Another set of analyses examined the effects of age on conduct problem-related decrements in P300. Smaller P300 amplitudes within the posterior scalp region were associated with a greater number of conduct problems among subjects younger than 16.5 years. Among subjects greater than this median age, the effects of these behaviors were only apparent over the frontal scalp. Conclusions: It is concluded that P300 decrements previously attributed to familial alcohol/substance dependence might be the result of a coincident increase in the prevalence of conduct disorder problems. The analysis of age interactions suggests that P300 amplitude decrements observed at posterior scalp sites among subjects with more conduct problems disappear at approximately 16 to 17 years of age. After that age, decrements in frontal brain function may begin to emerge in the subset of conduct problem subjects who are at risk for developing adult antisocial personality disorder.